A Nineteenth-Century Mackenzie Inuit Site near Inuvik, Northwest Territories - Arnold, Charles D. (ARCTIC, 1986)
A small collection of artifacts obtained from an aboriginal Mackenzie Inuit grave eroded by the Mackenzie River is described. The site appears to date to within the second half of the 19 century, following European contact but before acculturative processes and population decline, which brought about the extinction of traditional Mackenzie Inuit culture.Key words: Inuit, archaeology, Mackenzie delta, nineteenth century, artifacts, erosion Mots clés: Inuit, archéologie, delta du Mackenzie, 19e siècle, artefacts, érosion